Pelatihan Pengelolaan Database Menggunakan XAMPP Untuk Meningkatkan Keterampilan Mahasiswa di Universitas Muhammadiyah Jambi - Kevin Kurniawansyah; Noneng Marthiawati; Hetty Rohayani; Hafiz Nugraha (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
This community service activity aimed to enhance students' technical skills in database management using XAMPP, an open-source platform that integrates Apache, MySQL, PHP, and phpMyAdmin. The program was implemented through a hands-on training approach based on experiential learning, allowing participants to practice installation, configuration, and database management independently. The results showed a significant improvement in students' understanding of database concepts and their ability to operate XAMPP effectively. Beyond technical competencies, the program also fostered behavioral changes, increased technological awareness, and the emergence of local leaders among the participants. This initiative is expected to contribute to the development of a more adaptive and collaborative learning culture in response to advancements in information technology.